National Strategy And Policy On The Agricultural Sector During The Covid-19 Outbreak - Supardi Rusdiana; Chalid Talib (SOCA: Jurnal Sosial Ekonomi Pertanian, 2020)
The spread of Covid-19 majorly affected the global economic stability. This major change also changed the dynamic of Indonesia economic growth. This study employed a literature study and discussion technique to analyze the situation during the spread of Covid-19. The data collected from the literature, websites, national and international news that relevant to the recent policies and conditions. This study aimed to know the strategy and policy taken by the national policymaker in the agricultural sector during the Covid-19 outbreak. Results showed that the impact of the spread of Covid-19 on the economic aspect and the strategy chosen depending on the national policies. The national policies made based on various aspects, risks, and market scenarios. The labor-intensive effort, development of the agricultural technology, and marketing efforts intensively done to engage the farmer and consumer. The long-term policies strengthen the national food security and agricultural sector. The policies of data use arranged to be applied in various sectors, especially agricultural and food security. These policies managed to encourage and accelerate the synergy of a sustainable agricultural modernization. The national food security development actively contributed to cope with the food security gap in all area in Indonesia. The long-term policies provided a better comprehension and behavior change toward the farmer wellness aspect.